Performance Of The National Zakat Agency Based On Financial Ratios - Lenap, Indria; Karim, Nina Karina; Sasanti, Elin Erlina (LPPM ISNJ Bengkalis, 2024)
This research aims to analyze the performance of BAZNAS Central Lombok Regency based on financial ratios. The type and research approach used is quantitative descriptive. This research uses secondary data from BAZNAS Central Lombok Regency financial reports for 2018-2022. The research results show that the activity ratio value indicates that BAZNAS Central Lombok has effectively distributed Zakat, Infaq, and Shadaqah (ZIS) funds. The turnover ratio shows very high/active performance, whereas the performance of ZIS fund distribution is excellent in time. The efficiency ratio shows that the ratio of collection costs is efficient, the operational cost ratio using the total operational costs divided by total ownership rights approach is inefficient, while the operational cost ratio using the total operational costs divided by total collection approach is efficient, as well as the human resource cost ratio. The amil fund ratio and liquidity ratio show good performance. On the other hand, the growth ratio shows poor performance. Theoretically, this research can be used as a reference for future research. Practically, this research can be a reference material for BAZNAS Central Lombok Regency, which has not yet entirely produced optimal performance and for the Central Lombok Regency government as the regulator so that it can mobilize the community and government officials in distributing zakat to BAZNAS Central Lombok Regency.